Synoptic and Mesoscale Analysis of Extreme Rainfall Event in Cilacap Meteorological Station, Indonesia on December 7, 2018 - Suwignyo Prasetyo; Wahyu Kurniawan; Inlim Ravijai Rumahorbo (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2021)
The highest rainfall for the last five years (2016-2020) was recorded at 199.5 mm in twenty-four hours at the Cilacap Meteorological Station. This study examines the dynamics of the atmosphere with a focus on the synoptic scale and the mesoscale analysis. This is done because high rainfall with a long duration is usually caused by clouds that grow due to wider-scale atmospheric circulation rather than only being influenced by local-scale convection. The outbreaks of cold air masses from the Asian highlands that propagates across the equator is the main cause on the synoptic scale. In addition, a fairly strong wind speed from the south supports convergence and triggers deep convective clouds by increasing the advection of warm air in the southern part of Java Island, especially in this case the Cilacap area. Meso-scale analysis was carried out using numerical simulations to estimate rainfall spatially and using Himawari-8 satellite imagery. Numerical simulations carried out using the Weather Research and Forecasting model with adjustments to certain parameterization schemes have not been able to estimate rainfall well enough with underestimated values compared to the observation data. Based on Himawari-8 satellite imagery, it is clearly observed that the cloud formed is a mesoscale convective cloud system with a life span of more than six hours. The cloud growth is quite massive, which is indicated by the cloud top temperature value is lower than -80℃ in the mature phase. Thus, the resulting rainfall includes extreme rain, resulting in flooding in parts of Cilacap.